"She looked to be in such total possession of her life” A Feminist Study of John Irving's "The World According to Grap" - Rasheed, Lamiaa Ahmed; Rasheed, Saba Ali Khalaf (International Journal of Psychosocial Rehabilitation, 2020)
John Irving's novels involve a combination of feelings, political concerns, and characters, mingles with a powerful descriptive details that mmake his writings fascinating and comprehensible. His most successful novel, "The World According to Garp", deals with the subject of feminism. There is a wide selection of female characters, who symbolize various feminist views. The themes that Irving expresses in his works are women’s abuse, sexual problems, gender issues and relationships, family and social circumstances, tragedy, death, the absurdity of good intentions, etc. But the very important subject is men’s violence against women, as in "The World According to Garp", which portrays a wounded woman violated by men's violence. The purpose of the current document is to address and examine Irving 's perceptions of the female characteristics as represented in "The World According to Garp's". Irving addresses several positive and feminism-friendly topics, and it seems like he continues to highlight the need for women's movements with equality. "The World According to Garp",(1987) discusses other facets of feminism, including the depiction of women as victims, and males as rapists, as well as, the sexual violence against women, that stems from the patriarchal society, which makes rape common, and something that women have to deal with in their community. The text provides a brief overview and analysis of both the issue of women's struggle to gain their rights, besides, to discuss radical movements and the significant activities relevant. Concrete descriptions of feminist attitudes in the book are explored in the practical part, then use the interpretation of feminist values. Feminist behavioral dimensions, sexual violence, and representation of women in western culture are discussed as important to this paper's theoretical section